Ulpian, Celsus and weed pollution of soil (D. 9. 2. 27. 14) - Aličić Samir (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
The subject of this paper is the analysis of meaning of Digest text D. 9. 2. 27. 14. An overview of different theories devoted to this text has been presented here with a critical review of their argumentation, and another possible way of interpretation has been proposed. The author draws the following conclusions based on comparative source analysis. It is certain that neither Celsus nor Ulpian in the text D. 9. 2. 27. 14 doubted that in the case of weed pollution of soil, interdict quod vi aut clam can be given since all conditions for its implementation were fulfilled. With the interdict only the damage caused within a year can be claimed. For this reason this procedural means belongs to either the land owner or, if the land is leased, to the leaseholder. For the same reason along with the interdict, Aquilian claim is given, provided that only one of the two procedural means can be used. It belongs to both the land owner and the lease holder. It is given to the lease holder for the damage caused before the expiry of the lease, and to the land owner for the one caused later. Therefore, the lease holder who uses Aquilian claim has to provide a procedural guarantee that the land owner will not by any subsequent claim request compensation for damages on the same grounds. The claim is given to the lease holder on the grounds of yield owner and not on the grounds of land owner. The claim is given both to the owner and the lease holder not as a direct, but as actio in factum ex lege Aquilia. The reason for this cannot be determined with certainty, as it is possible that Ulpian quoted Celsus's opinion in a different context from the original one.